Too hot to handle : - Close, Frank (Penguin, 1992)
Frank Close, a leading physicist and talented popular science writer, reveals the true story of the cold fusion controversy--a story ignored until now in spite of the glare of publicity surrounding Martin Fleischmann and Stanley Pons. On March 23, 1989, these two Utah scientists held an astonishing press conference, maintaining that they had succeeded, working in secret, in harnessing atomic fusion...